Does zero tillage save or increase production costs? Evidence from smallholders in Kyrgyzstan - Abdusame Tadjiev; Nodir Djanibekov; Thomas Herzfeld (International Journal of Agricultural Sustainability, 2023)
Promoting zero tillage has been recognized as an important strategy for smallholders from an agronomic perspective. However, the economic effects of adopting zero tillage are still a matter of debate. Employing an endogenous switching regression model on the plot-level panel data of 878 Kyrgyzstan's smallholders, we investigate the determinants of decision to adopt zero tillage and its effect on smallholders' production costs. We find that the probability of zero tillage adoption is associated with employment in agriculture, assets, agricultural shocks, fertilizer use, number of plots and average distances from dwelling to household fields and to main road. Furthermore, the results indicate that zero tillage adoption decreases land preparation costs by 23%, but increases hired labour and herbicide costs by 13% and 15%, respectively compared to conventional tillage method. Nevertheless, zero tillage can reduce total production costs by 15%. Our findings suggest that zero tillage can be promoted as an option for resource-scarce smallholders, especially to those in remote areas with poor access to inputs and machinery services. Promoting zero tillage adoption as a labour-saving or herbicide reducing practice can create false expectations among smallholders.
Keywords: 630; zero tillage; resource saving; production costs; endogenous switching regression; Central Asia